The Effect of Virtual Training on the Care Burden of Caregivers to Patients with Breast Cancer - Maryam Nouri; Nasrin Jafari Varjoshani; Zeinab Ghahremani; Farzane Ahmadi (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Breast cancer is still a major health concern, causing stress not only for the patients but also for their caregivers. Objectives: The aim of the present study was to determine the effect of virtual training on the care burden of caregivers to patients with breast cancer. Methods: This clinical trial was conducted on 80 caregivers of patients with breast cancer referred to the Mehraneh Clinic of Zanjan, Iran, in 2022. The participants were chosen by convenience sampling and randomly divided into the experimental and control groups using the block randomization method. A demographic information questionnaire along with the Zarit care burden questionnaire were used to collect data. The care burden of caregivers was determined before, immediately after, and one month after the intervention. The data were analyzed in SPSS 26 software using descriptive and inferential statistics (the independent t-test, Chi-square test, Mann-Whitney test, Fisher's exact test, and a marginal model for longitudinal data). Results: According to the results, the mean (SD) age of the caregivers was 42.20 (11.54) years, of whom 60% were male. Based on the longitudinal marginal model, no significant difference in care burden was observed between the two groups immediately after the intervention (P=0.077); however, this difference was statistically significant one month after the intervention (P<0.001). Conclusion: According to the findings, the virtual training intervention reduced the care burden of caregivers of patients with breast cancer in the long term. Therefore, providing training related to care burden reduction through cyberspace and social media can be suggested as a suitable and available method